2015
DOI: 10.1590/1415-52732015000200010
|View full text |Cite
|
Sign up to set email alerts
|

Cardápios e sustentabilidade: ensaio sobre as diretrizes do Programa Nacional de Alimentação Escolar

Abstract: O Programa Nacional de Alimentação Escolar é uma das políticas públicas brasileiras que têm estabelecido estreito diálogo com os princípios da Política Nacional de Segurança Alimentar e Nutricional e da Agroecologia. Diretrizes de execução, alinhadas com a temática da sustentabilidade, foram estabelecidas pela Lei nº 11.947, promulgada em julho de 2009, que estipula recursos para a compra de alimentos produzidos pela agricultura familiar, preferencialmente orgânicos, revelando preocupações ambientais e sociais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
50

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 9 publications
0
18
0
50
Order By: Relevance
“…And besides, large cities need large amounts of foods, which can only be supplied by cooperatives with high production volumes. Sousa et al 22 reported that the logistics needed by a family farm to meet PNAE demands in large urban areas depend on complex and costly schemes; it is a challenge for family farmers to outbid distributors and wholesalers from the conventional food supply system. Processed foods were requested by the public procurements within rural family farming of 41.42% of the cities.…”
Section: Discussionmentioning
confidence: 99%
“…And besides, large cities need large amounts of foods, which can only be supplied by cooperatives with high production volumes. Sousa et al 22 reported that the logistics needed by a family farm to meet PNAE demands in large urban areas depend on complex and costly schemes; it is a challenge for family farmers to outbid distributors and wholesalers from the conventional food supply system. Processed foods were requested by the public procurements within rural family farming of 41.42% of the cities.…”
Section: Discussionmentioning
confidence: 99%
“…Um dos grandes desafios no momento de planejar os cardápios refere-se ao incentivo à sustentabilidade [20] . Santos et al [21] avaliaram como insuficiente a inserção de alimentos orgânicos na alimentação escolar de municípios integrantes dos territórios rurais do Rio Grande do Sul.…”
Section: Discussionunclassified
“…A produção local insuficiente, a falta de certificado, o elevado custo, a desorganização dos órgãos envolvidos e uma forte presença da agricultura convencional foram os principais problemas citados pelos gestores [21] . Para viabilizar a presença desses alimentos seria necessária maior articulação dos gestores com os agricultores, visando programar a oferta e planejar a produção, respeitando-se a diversidade agrícola [20] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Para o sucesso desta inserção, o cardápio deve ser aceito pelos escolares, sendo que a escola, assim como a família, tem papel essencial na formação de hábitos alimentares saudáveis (RAMOS, 2011;SOUSA et al, 2015).…”
Section: Introductionunclassified